On the formation of foreign language written communicative competence of students of language specialties based on a methodological system using social network services - Kruzhkova, E.V.; Kumpeisova, V.S.; Smolyaninov, V.D. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
This article presents a methodological system developed by the authors for forming foreign-language written communicative competence of students of language specialties based on social services. In the methodology of foreign language education, there is a tendency to an increasing role of written speech due to the socioeconomic needs of modern society. The formation and development of the ability to create written statements in a foreign language remain problematic tasks at all levels of foreign language teaching. Modernization of education affects the expansion of educational technologies and electronic learning tools. Modern information and communication technologies provide additional opportunities for students to move to a more advanced level of formation of foreign-language written communicative competence, which is understood as the ability to carry out foreign-language written speech activity with the help of a complex of linguistic knowledge and speech skills and abilities to create a foreign-language written text in accordance with the communicative situation. Social network services Instagram, Twitter, and others, which allow users to transmit written messages, have a number of didactic properties and methodological functions with the possibility of their use in the foreign language educational process. The authors describe the main components of the methodological system, the methodological conditions for the formation of a foreign written communicative competence, the conducted experiment, and its results. The analysis of experimental teaching confirms the positive dynamics of indicators of the degree of formation of foreign-language written communicative competence of students of language specialties in all aspects: possession of methods of constructing a foreign-language written statement adequately to the language situation, the formation of socio-cultural, sociolinguistic, linguistic competencies, high motivation, and adequate self-esteem.
Әлеуметтік қызметтерді пайдалана отырып, әдістемелік жүйе негізінде тіл мамандықтары студенттерінің шетел тілі жазбаша коммуникативтік құзыреттілігін қалыптастыру туралы
О формировании иноязычной письменной коммуникативной компетенции студентов языковых специальностей на основе методической системы с использованием социальных сервисов
Keywords: written speech; competence; formation of foreign language written communicative competence; social networks; online services; ICT; methodological system; teaching tools; students of language specialties